Pathways From Religion to Advance Care Planning: Beliefs About Control Over Length of Life and End-of-Life Values - Garrido, Melissa M. (Oxford University Press, 2013)
Purpose of the Study: To evaluate the extent to which religious affiliation and self-identified religious importance affect advance care planning (ACP) via beliefs about control over life length and end-of-life values. Design and Methods: Three hundred and five adults aged 55 and older from diverse racial and socioeconomic groups seeking outpatient care in New Jersey were surveyed. Measures included discussion of end-of-life preferences; living will (LW) completion; durable power of attorney for healthcare (DPAHC) appointment; religious affiliation; importance of religion; and beliefs about who/what controls life length, end-of-life values, health status, and sociodemographics. Results: Of the sample, 68.9% had an informal discussion and 46.2% both discussed their preferences and did formal ACP (LW and/or DPAHC). Conservative Protestants and those placing great importance on religion/spirituality had a lower likelihood of ACP. These associations were largely accounted for by beliefs about God’s controlling life length and values for using all available treatments. Implications: Beliefs and values about control account for relationships between religiosity and ACP. Beliefs and some values differ by religious affiliation. As such, congregations may be one nonclinical setting in which ACP discussions could be held, as individuals with similar attitudes toward the end of life could discuss their treatment preferences with those who share their views.